2020
DOI: 10.5194/cp-16-713-2020
|View full text |Cite
|
Sign up to set email alerts
|

Dansgaard–Oeschger-like events of the penultimate climate cycle: the loess point of view

Abstract: Abstract. The global character of the millennial-scale climate variability associated with the Dansgaard–Oeschger (DO) events in Greenland has been well-established for the last glacial cycle. Mainly due to the sparsity of reliable data, however, the spatial coherence of corresponding variability during the penultimate cycle is less clear. New investigations of European loess records from Marine Isotope Stage (MIS) 6 reveal the occurrence of alternating loess intervals and paleosols (incipient soil horizons), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 76 publications
0
14
0
1
Order By: Relevance
“…Ice-core records from the Greenland, and deep-sea sediment records from the North Atlantic Ocean highlight these prominent DO glacial events. Paleoclimatic studies have now shown that the 1500-year climate cycle is no longer restricted to the North Atlantic Ocean of the last glacial period 3 . The 1500-year cycle is documented in both hemispheres, in other oceans and in continents, such as in lake and river deposits 4 6 , in pollen fossils 7 , in stalagmite proxy records 8 , and in loess–paleosol deposits 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Ice-core records from the Greenland, and deep-sea sediment records from the North Atlantic Ocean highlight these prominent DO glacial events. Paleoclimatic studies have now shown that the 1500-year climate cycle is no longer restricted to the North Atlantic Ocean of the last glacial period 3 . The 1500-year cycle is documented in both hemispheres, in other oceans and in continents, such as in lake and river deposits 4 6 , in pollen fossils 7 , in stalagmite proxy records 8 , and in loess–paleosol deposits 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Phases of loess deposition are generally linked to harsh environmental conditions. In contrast, phases showing an interruption of loess deposition as indicated by surface exposure and the initiation of soil forming processes are generally assumed to indicate more favorable environmental conditions that often accompanied Greenland interstadials (GI, e.g., Fischer et al, 2021) and are therefore interpreted as D-O-like events (Rousseau et al, 2017(Rousseau et al, , 2020. Based on variations of NGRIP δ 18 O and dust concentration, Rousseau et al (2017) calculated onset and duration of the various GIs in the Northern Hemisphere during the last glacial period and found a strong conformity between higher GI duration and more intense soil development in northwestern Europe as indicated by loess-paleosol sequences (LPS).…”
Section: Phases Of Soil Developmentmentioning
confidence: 99%
“…Loess sediment in the mid-latitude of Eurasia provides an excellent sedimentary archive for understanding past climate and environmental changes in the continental interior (e.g., Rousseau et al, 2017Rousseau et al, , 2020Fenn et al, 2020;Fitzsimmons et al, 2020;Költringer et al, 2020;Song et al, 2021). In northern Iran, loess deposits are found in the so-called Northern Iranian Loess Plateau (NILP) and along the northern foothills of the Alborz Mountain range (NFAM).…”
Section: Introductionmentioning
confidence: 99%